Coparentality and Parental Involvement in Binuclear Families: Systematic Literature Review - de Souza, Fernanda Martins (2020)
Objective. The objective of this systematic review was to understand how coparenting, parental involvement, and parenting practices influence the dynamics of binuclear families. Method. A search was carried out in the PsycINFO, Web of Science, and BVSPsi databases, which resulted in 17 scientific articles. The studies were analyzed critically concerning the methodological characteristics and the main results. Results. In general, it was observed that coparenting and parental involvement are associated with several factors that protect the psychological health of parents and children after divorce, in line with data found with intact/nuclear families. No research was found on parenting practices within the established search criteria. Possible biases and indications for future investigations and interventions with binuclear families are discussed.